Length of loop

Calculus Level 5

9 y 2 = ( x 3 ) ( x 6 ) 2 \large{9y^2=(x-3)(x-6)^2}

Given the length of the closed loop of the curve above is a b {a\sqrt{b}} for positive integers a a and b b with b b is square free integer. Evaluate a × b a\times b .

Try this .


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jul 19, 2015

From the graph, we note that the loop is between 3 x 6 3 \le x \le 6 . The length of the loop is given by:

s = 2 3 6 1 + ( d y d x ) 2 d x = 2 3 6 1 + ( x 4 ) 2 4 ( x 3 ) d x [ See Note ] = 2 3 6 4 x 12 + x 2 8 x + 16 4 ( x 3 ) d x = 2 3 6 x 2 4 x + 4 4 ( x 3 ) d x = 3 6 x 2 x 3 d x [ Let u 2 = x 3 x = u 2 + 3 d x = 2 u d u ] = 0 3 u 2 + 3 2 u 2 ( 2 u ) d u = 2 0 3 ( u 2 + 1 ) d u = 2 [ u 3 3 + u ] 0 3 = 2 [ 3 + 3 ] = 4 3 \begin{aligned} s & = 2 \int_3^6 \sqrt{1+\color{#3D99F6} {\left(\frac{dy}{dx}\right)^2}} dx \\ & = 2 \int_3^6 \sqrt{1+\color{#3D99F6} {\frac{(x-4)^2}{4(x-3)}}} dx \quad \quad \color{#3D99F6}{[\text{See Note}]} \\ & = 2 \int_3^6 \sqrt{\frac{4x-12 + x^2 - 8x + 16}{4(x-3)}} dx = 2 \int_3^6 \sqrt{\frac{x^2 - 4x + 4}{4(x-3)}} dx \\ & = \int_3^6 \frac{x - 2}{\sqrt{x-3}} dx \quad \quad \color{#D61F06} {[\text{Let }u^2 = x - 3 \Rightarrow x = u^2 + 3 \Rightarrow dx = 2u\space du]} \\ & = \int _{\color{#D61F06}{0}}^{\color{#D61F06}{\sqrt{3}}} \frac{\color{#D61F06}{u^2+3}- 2}{\sqrt{\color{#D61F06}{u^2}}} \color{#D61F06}{(2u)du} = 2 \int_0^{\sqrt{3}} (u^2+1) du \\ & = 2 \left[\frac{u^3}{3} + u \right]_0^{\sqrt{3}} = 2 \left[\sqrt{3}+\sqrt{3}\right] = 4\sqrt{3} \end{aligned}

a × b = 4 × 3 = 12 \Rightarrow a \times b = 4 \times 3 = \boxed{12}

Note: \color{#3D99F6} {\text{Note:}}

9 y 2 = ( x 3 ) ( x 6 ) 2 18 y d y d x = ( x 6 ) 2 + ( x 3 ) ( 2 ) ( x 6 ) d y d x = ( x 6 ) ( x 6 + 2 x 6 ) 18 y = ( x 6 ) ( x 4 ) 6 y ( d y d x ) 2 = ( x 6 ) 2 ( x 4 ) 2 36 y 2 = ( x 6 ) 2 ( x 4 ) 2 4 ( x 3 ) ( x 6 ) 2 = ( x 4 ) 2 4 ( x 3 ) \begin{aligned} 9y^2 & = (x-3)(x-6)^2 \\ 18 y \frac{dy}{dx} & = (x-6)^2 + (x-3)(2)(x-6) \\ \frac{dy}{dx} & = \frac{(x-6)(x-6+2x-6)}{18 y} = \frac{(x-6)(x-4)}{6y} \\ \color{#3D99F6} {\left( \frac{dy}{dx} \right)^2} & = \frac{(x-6)^2(x-4)^2}{36y^2} = \frac{(x-6)^2(x-4)^2}{4(x-3)(x-6)^2} = \color{#3D99F6}{\frac{(x-4)^2}{4(x-3)}} \end{aligned}

Moderator note:

Simple standard approach using Arc Length.

You don't need to draw the graph. you just need to show that it's symmetric about the x x -axis and the loop is the interval [ 3 , 6 ] [3,6] .

Pi Han Goh - 5 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...